Verification of the Introgression of Narenga porphyrocoma Germplasm into Saccharum officinarum Using Molecular Markers and GISH Analysis - Gang Wang; Wei Zhang; Yuanxia Qin; Qingdan Wu; Qinggan Liang; Jiantao Wu; Shengren Sun; Zhuqing Wang; Yuxing An; Jianqiang Wang; Qinnan Wang; Hailong Chang (Agronomy)
Sugarcane (Saccharum spp.), a critical crop for sugar and bioenergy production, faces challenges in genetic improvement due to limited genetic diversity from selective breeding. Expanding genetic resources through intergeneric hybridization, particularly with Narenga porphyrocoma, offers a promising avenue to introduce traits like stress resistance and high biomass productivity. However, verifying true hybrids remains challenging with traditional morphological methods. This study employed tetra-primer ARMS-PCR and genomic in situ hybridization (GISH) to accurately identify intergeneric hybrids between S. officinarum and N. porphyrocoma. Species-specific primers were designed based on SNPs in the nrDNA-ITS region for ARMS-PCR, enabling effective differentiation of parental and hybrid genotypes, while GISH confirmed the chromosomal composition of hybrids, revealing an n + n inheritance pattern. The results demonstrated the potential of N. porphyrocoma to improve sugarcane’s tillering and leaf length, although sucrose content was lower in hybrids, suggesting the need for further breeding efforts. This study uniquely contributes to sugarcane breeding by providing an effective method for hybrid verification and laying a foundation for incorporating beneficial N. porphyrocoma genes into sugarcane cultivars.